Upaya Meningkatkan Kompetensi Guru Sasaran dalam Penyusunan RPP Melalui Pendampingan Berbasis MGMP di SMA Negeri 2 Mataram - Andrasto, Kun (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this study is to determine the effectiveness of MGMP-based mentoring in an effort to improve teacher competence in preparing a good and correct RPP. The method of this study using the method of school action research. This study was conducted in two cycles, each cycle twice a meeting. The stages of each cycle are planning, execution, observation, and reflection. The indicators of success in this study are; 1) the results of principal observation and teacher observation during the mentoring process has obtained the average score> 4.0, 2) teacher work in the preparation of RPP reach> 85% with the average value> 80.00. The result of the research in cycle I was observed by the principal average (3.50), average teacher observation (3.63) and average individual work result value (60.28) with percentage of achievement (0%). In cycle II the mean principal observation (4.60), average teacher observation (4.25) and average individual work result value (91.39) with percentage of achievement (100%). The success indicator has been reached, the research stated successful and stopped in cycle II. The conclusion obtained from the results of this study is the implementation of assistance can improve the competence of target teachers SMA Negeri 2 Mataram in the preparation of good and correct RPP based on KTSP.